2019
DOI: 10.1108/ejmbe-12-2017-0068
|View full text |Cite
|
Sign up to set email alerts
|

The impact of perceived CSR on corporate reputation and purchase intention

Abstract: Purpose The purpose of this paper is to examine the influence of consumers’ perceived corporate social responsibility (CSR). The aim is to provide insight into the effect of perceived CSR on purchase intention (short-term effect) and corporate reputation (long-term effect), whilst considering the role of brand image, satisfaction (affective and cognitive) and brand loyalty. Design/methodology/approach The sample comprised 429 consumers selected using non-probabilistic sampling with age and gender quotas. Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
147
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 177 publications
(210 citation statements)
references
References 66 publications
14
147
0
2
Order By: Relevance
“…This is in line with the results of previous research, according to which a strategy of differentiation in the foreign market based on CSR favors the EXP of companies [70][71][72]. The results also confirm, in line with numerous previous works [18,[78][79][80][81][82][83][84], the existence of a positive impact of the CSR of the companies in the sector on their IR. Finally, in line with other previous work [37,[86][87][88][89][90][91][92][93][94][95][96], the existence of a positive impact of CSR on SS is also confirmed.…”
Section: Theorical Implicationssupporting
confidence: 92%
See 1 more Smart Citation
“…This is in line with the results of previous research, according to which a strategy of differentiation in the foreign market based on CSR favors the EXP of companies [70][71][72]. The results also confirm, in line with numerous previous works [18,[78][79][80][81][82][83][84], the existence of a positive impact of the CSR of the companies in the sector on their IR. Finally, in line with other previous work [37,[86][87][88][89][90][91][92][93][94][95][96], the existence of a positive impact of CSR on SS is also confirmed.…”
Section: Theorical Implicationssupporting
confidence: 92%
“…CSR positively influences the opinions of stakeholders and is considered to be a sign that the company will take into account their interests and expectations [78,79], opinions, which, in short, form the basis of its reputation [80]. There are numerous works that show a positive relationship between CSR and IR in different economic sectors [18,[78][79][80][81][82][83][84]. In line with these findings, we propose the following hypothesis: Hypothesis 3 (H3): Firms' CSR orientation is positively related to their image and reputation.…”
Section: Csr and Image And Reputationmentioning
confidence: 99%
“…Moreover, the motive for buying goods and the evaluation of the company is also influenced by CSR activities. In other words, the company develops communications of CSR activities to stimulate evaluations of the brand [53], to generate a positive relationship with a corporate reputation [54][55][56], and to integrate CSR practices into their business strategy to position the brand [57]. This leads to the following hypothesis:…”
Section: Corporate Social Responsibility and Perceived Reputationmentioning
confidence: 99%
“…Yet, studies have found that there is a relationship between CSR performance and customer's support intentions (Abdeen, Rajah, & Gaur, 2016; Jose, Khare, & Buchanan, 2015). It is well documented that consumers' perceptions of CSR have a positive impact on their purchase intentions (Alniacik, Alniacik, & Genc, 2011; Bianchi, Bruno, & Sarabia‐Sanchez, 2019; Jones, Reilly, Cox, & Cole, 2017; Mohr, Webb, & Harris, 2001; Pekkanen, Pätäri, Albadera, & Jantunen, 2018; Sen, Bhattacharya, & Korschun, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…well documented that consumers' perceptions of CSR have a positive impact on their purchase intentions (Alniacik, Alniacik, & Genc, 2011;Bianchi, Bruno, & Sarabia-Sanchez, 2019;Jones, Reilly, Cox, & Cole, 2017;Mohr, Webb, & Harris, 2001;Pekkanen, Pätäri, Albadera, & Jantunen, 2018;Sen, Bhattacharya, & Korschun, 2006).…”
mentioning
confidence: 99%